RETRACTED: Machine learning insights into log files with ML.NET for real-time farm monitoring - Nuriev Marat; Zaripova Rimma; Filimonova Tamara; Kuznetsov Maxim (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001